Предмет: Математика,
автор: Lanskaya777
Решите уравнение (х^2-16)^2+(х^2+х-12)^2=0
Ответы
Автор ответа:
0
((x - 4)*( x + 4))^2 + ((x + 4)*(x - 3))^2 = 0
(x + 4)^2 ( (x - 4)^2 + (x - 3)^2) = 0
( x + 4)^2 * ( x^2 - 8x + 16 + x^2 - 6x + 9) = 0
(x + 4)^2 * ( 2x^2 - 14x + 25) = 0
2x^2 - 14x + 25 = 0
D = 196 - 4*2*25 < 0
нет реш
(x + 4)^2 = 0
x = - 4
Ответ:
- 4
(x + 4)^2 ( (x - 4)^2 + (x - 3)^2) = 0
( x + 4)^2 * ( x^2 - 8x + 16 + x^2 - 6x + 9) = 0
(x + 4)^2 * ( 2x^2 - 14x + 25) = 0
2x^2 - 14x + 25 = 0
D = 196 - 4*2*25 < 0
нет реш
(x + 4)^2 = 0
x = - 4
Ответ:
- 4
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Английский язык,
автор: KimYuri
Предмет: Другие предметы,
автор: zoga380
Предмет: Математика,
автор: abilovzanat6
Предмет: Алгебра,
автор: ivanant79